Pergeseran Gaya Estetis Mebel di Keraton Ngayogyakarta Hadiningrat - Indah Septi; Agus Sachari (Journal of Visual Art and Design, 2007)
The Kraton Ngayogyakarta Hadiningrat has been the center for the development of ideas, traditions, and cultural artifacts, giving it a unique status among Indonesia diverse cultures. Understanding the richness of Yogya's inherited artifacts, this research tried to investigate the existing styles of furniture in the Keraton Ngayogyakarta Hadiningrat during 1755 to 1988. The span period was chosen because during that time the Keraton endured several cultural transformations, from the period where Hindu-Buddha was very much influential to the era of colonialism. Sources for this research were gained through direct observation, interview and documentation, amplifying descriptive qualitative method using historical approach for analysis. The study indicates that there exist visual data, left by Sri Sultan Hamengku Buwono VIth to IXth, in form of symbolic mean that could be seen on the furniture (ornaments) in the Keraton Ngayogyakarta Hadiningrat. It shows that the most frequent used ornaments are geometric shape, flora-fauna, and imaginary creatures. The ornaments are usually placed at the top, center and lower parts of the furniture. Aside to fulfill aesthetical decoration, those ornaments, which also have symbolic mean, are used as a medium to express the social norms of the Kraton Ngayogyakarta Hadiningrat.